Excel 2010 for Social Science Statistics : A guide to solving practical statistics problems - Quirk, Thomas J. (New York ; London : Springer, 2012)
Explaining statistical theory and formulas without recourse to complex mathematics, this text deploys exemplars, screenshots and exercises to show just how adaptable Excel 2010 can be to solving statistical problems in a range of social science subjects.
Keywords: Microsoft Excel (Computer file); Electronic spreadsheets -- Computer programs; Social sciences -- Statistical methods -- Computer programs; Society